Exploring how arm movement moderates the effect of lower limb muscle fatigue on dynamic balance in healthy youth - Borgmann, Katharina; Ferdenhert, Jendrik; Neyses, Alexandra C.; Bauer, Julian; Hill, Mathew W.; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2024)
Background In young adults, there is evidence that free arm movements do not help to compensate muscle fatigue-induced deteriorations in dynamic balance performance. However, the postural control system in youth is immature, and as a result, the use of arm movements may provide a compensatory “upper body strategy” to correct fatigue-related balance impairments. Thus, the purpose of the present study was to compare the effects of free vs. restricted arm movement on dynamic balance performance prior and following exercise-induced muscle fatigue. Methods Forty-three healthy youth (19 females; mean age: 12.8 ± 1.9 years) performed the Y Balance Test–Lower Quarter before and immediately after a fatiguing exercise (i.e., repetitive vertical bipedal box jumps until failure) using two different arm positions: free (move the arms freely) and restricted (keep the arms akimbo) arm movement. Results Muscle fatigue (p ≤ 0.033; 0.10 ≤ ηp2 ≤ 0.33) and restriction of arm movement (p ≤ 0.005; 0.17 ≤ ηp2 ≤ 0.46) resulted in significantly deteriorated dynamic balance performance. However, the interactions between the two did not reach the level of significance (p ≥ 0.091; 0.01 ≤ ηp2 ≤ 0.07). Conclusion Our findings indicate that the use of an “upper body strategy” (i.e., free arm position) has no compensatory effect on muscle fatigue-induced dynamic balance deteriorations in healthy youth.